An analysis of the Chinese translation of Singapore Financial Reporting Standards related to agriculture - Chew, Kim Kuan (2019)
Translation of accounting and financial reporting standards related to agriculture is a type of specialised translation. The accounting and financial reporting standards related to Agriculture, which are applied in Singapore, are mainly based on Singapore Financial Reporting Standard (International) 1-41- Agriculture which is equivalent to International Accounting Standard 41(IAS 41). This paper presents an analysis of the Chinese translation of accounting and financial reporting standards, which discusses the similarities and differences of three versions of the Chinese translation of IAS 41 from three different countries, i.e. Taiwan, China and Singapore, evaluation of machine translation of IAS 41, and challenges of translating IAS 41. The comparison of these three versions of the Chinese translation focused on the principles of translation and translation strategy, and consistency and accuracy in translation, including translation of key terms in financial reporting standards. In addition, the Singaporean version of translation was produced by the author of this paper herself, who is a professional Chartered Accountant with more than ten years of experience working in companies dealing with international business. There are a few valuable findings in this study. Firstly, the translation of accounting and financial reporting standards is mainly sense-for-sense translation and the translation of some key accounting terms which are commonly used may not be identical in different countries. Secondly, machine translation is more reliable at this juncture, which can assist in increasing the efficiency of translating accounting and financial reporting standards. However, we should have reservations about depending on it fully due to disadvantages of the machine translation. Thirdly, the Chinese translation of accounting and financial reporting standards may be challenging for a translator as he or she needs to possess linguistic competence, a good understanding of the source text as well as accounting and financial reporting standards, and logical thinking in translation. Finally, Chinese translation of International Financial Reporting Standards or IAS may involve team work to improve the quality of translation.